Understanding antimicrobial susceptibility profile of Finegoldia magna: an insight to an untrodden path - Seema Shetty; Renuka Anegundi; Padmaja Ananth Shenoy; Shashidhar Vishwanath (BMC, 2023)
Abstract Background Finegoldia magna (formerly known as Peptococcus magnus or Peptostreptococcus magnus) belonging to phylum Firmicutes, class Clostridia and genus Finegoldia, is the only species known to cause infections in human beings. Amongst Gram positive anaerobic cocci, F. magna is known to be the most virulent with a high pathogenic potential. Significant upsurge in antimicrobial resistance among anaerobes has been documented by various studies. F. magna is known to be susceptible to most of the anti-anaerobic antimicrobials, however, multidrug resistant strains are being reported in literature. The present study was undertaken to highlight the role of F. magna in clinical infections and to analyze their antimicrobial susceptibility patterns. Methods The present study was conducted in a tertiary care teaching hospital in Southern India. 42 clinical isolates of F. magna recovered from diverse clinical infections between January 2011 to December 2015 were studied. These isolates were subjected to antimicrobial susceptibility testing against metronidazole, clindamycin, cefoxitin, penicillin, chloramphenicol and linezolid. Results Among the 42 isolates studied, majority of them were revived from diabetic foot infections (31%) followed by necrotizing fasciitis (19%) and deep-seated abscesses (19%). All the F. magna isolates showed good in-vitro activity against metronidazole, cefoxitin, linezolid and chloramphenicol. Clindamycin and penicillin resistance were observed against 9.5% and 2.4% of the isolates respectively. However, β-lactamase activity was not detected. Conclusion The antimicrobial resistance among anaerobes varies from pathogen to pathogen and region to region. Hence, a deep understanding of resistance pattern is necessary for better management of clinical infections.